Government Actions And The Mineral Industry (The National Institute for Occupational Safety and Health (NIOSH), 1980)
Lead Tariff.--The full House Ways and Means Committee approved H.R. 6089 which will have the effect of reducing the tariff on unwrought lead to 3% ad valorem, with a floor duty of 1.0625 cents per pound, compared with the currently effective rate of 3.5% ad valorem. Consideration is also being given to tariff rates on imports of red lead and litharge from Mexico. A consortium of domestic producers has appealed to the Office of the Special Trade Representative (STR) requesting a return to tariff schedules which were in effect prior to the concessions made effective on January 1. Mexican producers have filed a proposal in favor of lower duties, and the matter now awaits a ruling by the STR. Ferrous Scrap Exports.--After holding public hearings and receiving public comments in May, the Department of Commerce announced that it would not institute formal monitoring of ferrous scrap exports, as requested by the Ferrous Scrap Consumers Coalition. The Department said, however, that it would follow the trend of scrap exports and prices. Ferrous scrap prices are currently low and supplies are reported to be adequate.